2013
DOI: 10.1007/s00234-013-1186-1
|View full text |Cite
|
Sign up to set email alerts
|

Implicating the long styloid process in cervical carotid artery dissection

Abstract: Length and contact distance of the styloid process are risk factors for CCAD, suggesting mechanical impingement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 13 publications
0
13
1
Order By: Relevance
“…8 Because intramural hematoma may distort ICA anatomy and change its position in relation to other fixed cervical structures, we believe that measurement of the distance between SP and the center of the structure formed by the hematoma and the arterial lumen describes a more reliable anatomical relation between these structures, even though it does not completely exclude the bias introduced by large position changes, such as those caused by pseudoaneurysms. Muthusami et al 9 also found a marginal association of longer SP length and shorter SP-ICA distance in ICAD patients when compared to controls; however, this study was conducted in a single center, included fewer cases, and used a different method to measure SP-ICA distance. 9 In contrast to the first two studies, 6,8 we found that the characteristics of the SP contralateral to ICAD were not significantly associated with dissection, which could explain the low frequency of bilateral ICAD.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…8 Because intramural hematoma may distort ICA anatomy and change its position in relation to other fixed cervical structures, we believe that measurement of the distance between SP and the center of the structure formed by the hematoma and the arterial lumen describes a more reliable anatomical relation between these structures, even though it does not completely exclude the bias introduced by large position changes, such as those caused by pseudoaneurysms. Muthusami et al 9 also found a marginal association of longer SP length and shorter SP-ICA distance in ICAD patients when compared to controls; however, this study was conducted in a single center, included fewer cases, and used a different method to measure SP-ICA distance. 9 In contrast to the first two studies, 6,8 we found that the characteristics of the SP contralateral to ICAD were not significantly associated with dissection, which could explain the low frequency of bilateral ICAD.…”
Section: Discussionmentioning
confidence: 86%
“…Muthusami et al 9 also found a marginal association of longer SP length and shorter SP-ICA distance in ICAD patients when compared to controls; however, this study was conducted in a single center, included fewer cases, and used a different method to measure SP-ICA distance. 9 In contrast to the first two studies, 6,8 we found that the characteristics of the SP contralateral to ICAD were not significantly associated with dissection, which could explain the low frequency of bilateral ICAD. However, this association was only marginally nonsignificant, which could be related to the sample size.…”
Section: Discussionmentioning
confidence: 86%
“…810) Direct mechanical contact was more common in patients with CAD than control subjects. 9) These studies imply longer styloid process and shorter stylo-ICA distance are the important risk factors causing CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Muthusami et al indicated that, when the distance was ≤5 mm, the odds ratio for the onset of arterial dissection was 7.58. 10) In Cases 1 and 2, initial MRI showed that stenosis of the internal carotid artery was located at a higher position in comparison with arteriosclerotic stenosis; dissection of the internal carotid artery was suspected. In addition, the distance between the lesion and styloid process end was 2-3 mm, suggesting the involvement of the styloid process in dissection of the internal carotid artery.…”
Section: Discussionmentioning
confidence: 94%